Spiral gradient dilution, a rapid method for determining growth responses and 50% effective concentration values in fungus-fungicide interactions - Forster, Helga; Adaskaveg, James; Kanetis, Loukas (My University, 2004)
A new technique, the spiral gradient dilution method, was evaluated for determining 50% effective concentrations (EC50 values) of fungicides for the inhibition of mycelial growth and conidial germination of various fungi. In this method, an agar medium is plated with a fungicide solution by means of a spiral plater, which applies the fungicide in a 2.5-log dilution in a continuous radial concentration gradient. Fungal inoculum is then placed along radial lines across the gradient. After incubation of the plates, distinct growth shapes were observed in different fungus-fungicide interactions. Mycelial growth responses to increasing fungicide concentrations ranged from abrupt to gradual transitions. Conidial germination responses were similar; in addition, distinct zones of confluent growth, nonconfluent growth, and outlier colonies were also identified, depending on the fungus-fungicide interaction. The fungicide concentration at the radial distance at which 50% reduction of growth or spore germination occurred, compared with growth or germination on unamended media, was calculated by a computer program. EC50 values were obtained for mycelial growth in 22 fungus-fungicide interactions and for conidial germination in five interactions. The fungi evaluated were members of the Zygomycota, Ascomycota, Basidiomycota, and Deuteromycota. Nine fungicides, belonging to six different chemical classes, were tested. EC50 values were compared with those obtained by the traditional agar dilution method. In linear regression analyses of the two methods, the models were highly significant (P < 0.01), and coefficients of determination (r2) were 0.92 for the mycelial growth assays and 0.94 for the conidial germination assays. Regression slopes were not significantly different from 1 (P > 0.05) with optimal program settings in the software. Estimated bias, coefficients of variation, and actual confidence intervals for the regression slope were 13.5%, 6.5%, and 1.14 ± 0.14 for the mycelial growth assays and 7.5%, 14.5%, and 1.08 ± 0.37 for the conidial germination assays. These analyses indicate that the spiral gradient dilution method is accurate and precise compared with the agar dilution method for calculating EC50 values of fungicides in continuous growth responses to fungicide concentration gradients
Keywords: Fungicides; Ascomycetes; Bacteria; Basidiomycetes; Fungi; Fungi imperfecti; Plant diseases; Open access publishing